Removability of an isolated singularity of solutions of the Neumann problem for quasilinear parabolic equations with absorption that admit double degeneration - Boldovskaya, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider the Neumann initial boundary-value problem for the equation u_t=div(u^m−1|Du|^λ−1Du)−u^p in domains with noncompact boundary and with initial Dirac delta function. In the case of slow diffusion (m + λ − 2 > 0) and critical absorption exponent (p = m + λ − 1 +λ + 1N), we prove that the singularity at the point (0, 0) is removable.